ANALISIS KEPUASAN PELANGGAN MASKAPAI DI KABUPATEN MIMIKA - Bonita Nicolina Hamid; Adrianus Tunabenany; Tri Apriyono (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2026)
This study aims to determine customer satisfaction with Lion Air and Wings Air Group at Mozes Kilangin Airport in Mimika. The method used in this study is the descriptive method, and the data analysis technique employed is descriptive statistical analysis of maximum, minimum and mean values, using SPSS statistical software. In this study, the data collection technique employed was the distribution of questionnaires. The results of this study indicate that, across the four factors, customer dissatisfaction with the airlines—specifically Lion Air and Wings Air—in Mimika Regency has been confirmed.